Cost effectiveness of the Expert Patients Programme (EPP) for patients with chronic conditions. Issue 4 (13th March 2008) - Richardson, G; Kennedy, A; Reeves, D; Bower, P; Lee, V; Middleton, E; Gardner, C; Gately, C; Rogers, A
Abstract : Objective: To assess the cost effectiveness of the Expert Patients Programme (EPP) intervention compared to a treatment as usual alternative. Design: Two-arm pragmatic randomised controlled trial design with waiting list control. Setting: Community settings in England. Patients: Patients with a wide range of self-defined long-term conditions. Intervention: The EPP based on the US chronic disease self management program (CDSMP), a lay-led self-care group involving six weekly sessions to teach self-care support skills. Main outcome measures: Costs estimated over a 6-month period from a societal perspective. Health outcomes estimated in terms of quality adjusted life years (QALYs) generated by patients' response to the EQ5D at baseline and 6-month follow-up. Results: The intervention group is associated with better patient outcomes, at slightly lower cost. Specifically, the intervention group has a 0.020 QALY gain compared with the control group, and a reduced cost of around £27 per patient. The intervention would therefore be considered dominant. While the QALYs gained are small in absolute terms, an additional 0.02 QALY is equivalent to an extra one week of perfect health per year. When the value of a QALY is £20 000 the EPP has a probability of 94% of being cost effective. Indeed, for all plausible values of willingness-to-pay for a QALY the EPP group is more likely to be cost effective than the control group. Conclusions: The EPP intervention evaluated in this trial is very likely to provide a cost effective alternative to usual care in people with long-term conditions.